Real Estate Strategic Development: A Systematic Literature Review of Real Estate Developer Strategy in The Area of Transit Oriented Development - M Akmal Alwee, Daffa; Gamal, Ahmad (Lafadz Jaya Publisher, 2024)
Real estate developers had a challenge from the COVID-19 pandemic era, since the pandemic era had been declared to an end, developers facing the urge of urbanisation and urban development throughout Transit-Oriented Development (TOD). This systematic literature review compares for which the strategy suits well into the TOD areas, the strategy based on the literature of Fred David about 11 business development strategy and its alternatives. This review will be exploring between those 11 strategies with its methods of research in each paper and in the end will reflecting into the TOD areas by its principles. Systematic research conducted from the Scopus and Google Scholar databases using the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA 2020) guideline to find relevant publications published between 2013 and 2023. The analysis will conclude 30 academic research to evaluate the connection between a real estate strategy and TOD Principles, in which strategies most likely suitable regarding the TOD principles. The articles that are taken from the Scopus and Google Scholar give insight into how TOD principles influence the real estate development strategy, based on the 11-business development strategy. The findings will emphasize the role of which strategy that complies various of TOD Principles. Understanding the TOD Principles to support real estate developer formulating variety of strategy. In the end this writing hopefully contributes to the knowledge between real estate developer and its external factors, that in this case is the TOD development. The Findings of this review emhpasize output to developer, urban planners and enthusiast who are interest in developing real estate near the areas of TOD.